A model of phototrophic sulfide oxidation in a stratified estuary. (26th March 2017) - Findlay, Alyssa J.; Di Toro, Dominic M.; Luther, George W.
Abstract: Sulfide accumulated as a result of microbial sulfate reduction in sediments and the bottom waters of stratified systems can be re‐oxidized via an array of biotic and abiotic reactions. A one‐dimensional diffusion‐reaction model was developed and applied to 4 yr of physical and chemical data from the stratified water column of the Chesapeake Bay in order to quantify the impact of different sulfide oxidation processes at the redox interface during slack tide. This dataset and the model simulations highlight short‐term and interannual variation in the physical structure and the distribution of key redox species (O2, H2 S, S 0, Fe 2+, Mn 2+, FeOOH, MnO2 ) throughout the water column. The model evaluates links between oxygen, sulfur, iron and manganese cycling, and includes the novel consideration of sulfide oxidation by phototrophic sulfide oxidizing bacteria (PSOB), which are a common component of the Bay. Model simulations demonstrate that phototrophic sulfide oxidation can account for up to 58% of total sulfide oxidation, depending upon the depth of the oxic/anoxic interface. The results of this study yield an approach to parameterizing PSOB activity, and quantify the variable role that PSOB play in sulfide oxidation in the Chesapeake Bay as redox conditions in the water column change, which has applications for both modern and ancient environments.